Effectiveness of lower limb arterial angioplasty - Anna Szuciak; Konrad Talarek; Julia Szewczyk; Michał Świta; Bartosz Skierkowski; Alicja Drelichowska; Przemysław Ciszewski; Michał Azierski; Damian Pikor (Quality in Sport, 2024)
Introduction: Over 200 million individuals worldwide suffer with peripheral artery disease (PAD). The disease makes it difficult to function properly by limiting walking and physical activity, which also translates into a reduced quality of life.